A Novel Handover Mechanism Between Femtocell and Macrocell for LTE Based Networks - Zhang, Haijun; Wen, Xiangming; Wang, Bo; Zheng, Wei; Sun, Yong (2010 Second International Conference on Communication Software and Networks, 2010)
The femtocell networks that use Home eNodeB and existing networks as backhaul connectivity can fulfill the upcoming demand of high data rate for wireless communication system as well as can extend the coverage area. It is also of interest to minimize operational effort by introducing self-optimizing mechanisms, and the optimization of the Home eNodeB involved handover is an important goal of LTE-Advanced. Since the different network architecture and functionality between Home eNodeB and LTE eNodeB, the handover procedure between the femtocell and macrocell should be modified in LTE network. In this paper, modified signaling procedure of handover is presented in the Home eNodeB gateway based femtocell network architecture. A new handover algorithm based on the UE's speed and QoS is proposed. The comparison between the proposed algorithm and the traditional handover algorithm shows that the algorithms proposed in this paper have a better performance in the reducing of unnecessary handovers and the number of handovers.